2016
DOI: 10.3389/fmicb.2016.00725
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide Toxicity to Burkholderia cenocepacia Is Modulated by Polymicrobial Communities and Environmental Factors

Abstract: Microbes within polymicrobial communities can establish positive and negative interactions that have the potential to influence the overall behavior of the community. Pseudomonas aeruginosa and species of the Burkholderia cepacia complex (Bcc) can co-exist in the lower airways, however several studies have shown that P. aeruginosa can effectively kill the Bcc in vitro, for which hydrogen cyanide (HCN) was recently proposed to play a critical role. Here we show that modification of the environment (i.e., cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 90 publications
0
30
0
Order By: Relevance
“…The chronicity of specific infections (27), their interactions with human host defenses, and their clinical outcomes have been studied previously (28). Microbial species-to-species interactions among pathogens similar to those found in the CF airway have been studied in various in vitro and nonhuman in vivo model systems (17,18,(29)(30)(31)(32)(33)(34)(35)(36)(37), and the clinical effects of the combination of P. aeruginosa and MSSA have been explored (38), but interspecies microbial interactions in the CF airway have been minimally explored, and recent calls to expand this knowledge base remain outstanding (16,39).…”
Section: Discussionmentioning
confidence: 99%
“…The chronicity of specific infections (27), their interactions with human host defenses, and their clinical outcomes have been studied previously (28). Microbial species-to-species interactions among pathogens similar to those found in the CF airway have been studied in various in vitro and nonhuman in vivo model systems (17,18,(29)(30)(31)(32)(33)(34)(35)(36)(37), and the clinical effects of the combination of P. aeruginosa and MSSA have been explored (38), but interspecies microbial interactions in the CF airway have been minimally explored, and recent calls to expand this knowledge base remain outstanding (16,39).…”
Section: Discussionmentioning
confidence: 99%
“…H111∆orbJ∆pchAB and PAO1∆pvdD∆pchEF vs. H111∆orbJ one would even expect stable species co-existence or mild B. cenocepacia dominance in the absence of interference competition. While we can only speculate about the specific strategies deployed by P. aeruginosa, it is well known that this species possesses several mechanisms to engage in interference competition, including the secretion of diffusible toxins such as cyanide (Bernier et al 2016) and pyocyanin (O'Brien and Fothergill 2017) and the use of contact-dependent killing systems like the type VI secretion system (Basler et al 2013). Overall, these considerations suggest that selection pressures for sensing competitors, as opposed to sensing co-operators, were much stronger in the evolutionary past of P. aeruginosa, with the competitive responses triggered simply overruling any benefits that could accrue through pyochelin green-beard cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of culture media, ranging from minimal media to rich and viscous sputum-like media, may shape the composition, organisation and susceptibility of the community. BERNIER et al [71] showed that B. cenocepacia became less susceptible to cyanide produced by P. aeruginosa in the complex synthetic CF medium (SCFM) compared to in an undefined rich medium. Physiological levels of serum albumin can decrease P. aeruginosa virulence by sequestering acyl homoserine lactone (AHL) quorum sensing molecules [72].…”
Section: Culture Conditionsmentioning
confidence: 99%